Association between exposure to urban neighborhood natural environments and human health: A systematic review of multiple exposure indicators - Xingcan Zhou; Kojiro Sho; Hongfei Qiu; Shenglin Chang; Qingya Cen (Environmental and Sustainability Indicators)
Exposure to the natural environment in urban neighborhoods is essential for community interventions to improve human health. Although cross-sectional evidence suggests potential benefits, the understanding regarding how to integrate stronger associations to improve natural environments remains lacking. This article synthesized longitudinal and experimental health evidence using different nature exposure indicators. We searched three databases (PubMed, Scopus, and Web of Science) for articles published through June 2024; cross-sectional studies lacking temporality and qualitative case studies were excluded, and 96 studies were selected after screening 16102 records. Nature exposure indicators were categorized into availability, accessibility, visibility, and perceptibility. Notably, most studies measured availability using vegetation indices and area proportions, whereas accessibility was often analyzed in combination with availability in multidimensional assessments. Recent increases in visibility and perceptibility assessments, though infrequent, generally revealed significant positive relationships with human health. Among the 167 associations identified, 81.4% exhibited positive relationships with health, of which 70.06% were statistically significant. The highest percentage of negative results was observed in respiratory and emotional health outcomes. Nonsignificant or negative associations could be related to buffer size, nature coverage, or socioeconomic factors, and should prompt future research to explore underlying mechanisms and expand health practices.